Analisis Jiwa Leadership Melalui Kegiatan Ekstrakurikuler Paskibra Pada Siswa Kelas V SD Negeri Srondol Wetan 02 - F, Faiqussabila; Aura, Fisabillah; Arifah, Siti Lilik Ulya; Nuryadi, Anisha Anggi; Maelani, Dea Ananda Eka; Kiptiyah, Siti Maryatul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The research "Analysis of the Spirit of Leadership through Paskibra Extracurricular Activities in Class V Students of SD Negeri Srondol Wetan 02" examines the effectiveness of extracurricular Paskibraka in developing students' leadership spirit. Qualitative descriptive methods are considered suitable for this research, of course with observation, interviews, documentation and literature study instruments. Identifying patterns as a form of data analysis in developing student leadership. Support from the school, committee and parents is very important in developing students' leadership skills. Supporting factors include facilities and infrastructure, student motivation, and experienced supervisors. However, there are inhibiting factors such as lack of motivation and supervision from supervisors. By overcoming these obstacles, the development of leadership skills in students can run more effectively and efficiently. Paskibra activities at SD Negeri Srondol Wetan 02 play an important role in forming students' leadership spirit, giving them strong communication skills, initiative, teamwork and responsibility for the future.